2010
DOI: 10.3109/15622975.2010.504860
|View full text |Cite
|
Sign up to set email alerts
|

A prospective comparative study of interaction between lithium and modified electroconvulsive therapy

Abstract: Though concurrent lithium is by and large safe during ECT, it benefits to maintain serum lithium level at lower end of therapeutic range. However, the findings can be applied to relatively young patients with no risk factors for ECT-complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1
1

Year Published

2011
2011
2025
2025

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(19 citation statements)
references
References 23 publications
0
17
1
1
Order By: Relevance
“…One prospective naturalistic study investigated the effects on ST in a cohort of patients receiving BT ECT (1 ms pulse width), with (N ¼ 27) and without (N ¼ 28) lithium. Differences in ST between groups were not found, although the small sample size, the relatively large titration steps and the non-systematic analysis of ST makes it difficult to extract conclusions [66]. Lithium intake during ECT has been classically cautioned because of the possibility of cognitive and confusional effects [3] and of increasing seizure duration [67e69].…”
Section: Discussionmentioning
confidence: 99%
“…One prospective naturalistic study investigated the effects on ST in a cohort of patients receiving BT ECT (1 ms pulse width), with (N ¼ 27) and without (N ¼ 28) lithium. Differences in ST between groups were not found, although the small sample size, the relatively large titration steps and the non-systematic analysis of ST makes it difficult to extract conclusions [66]. Lithium intake during ECT has been classically cautioned because of the possibility of cognitive and confusional effects [3] and of increasing seizure duration [67e69].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies report that benzodiazepines may affect seizure duration, rather than threshold [59]; however, the use of flumazenil can potentially reverse their effect. While the use of lithium with ECT is generally safe, it is reasonable to keep its serum level at the lower end of the therapeutic range, as its serum level directly correlates with time to postictal recovery [60]. Although no definitive evidence supports the absolute contra indication of these medications, whenever possible, their use should be avoided during the ECT course.…”
Section: Ect Administrationmentioning
confidence: 96%
“…Literature describing an interaction between lithium and succinylcholine has been in the context of prolonged apnea [5,12,15] which this patient did not experience. However, Lithium's interaction with the Neuromuscular blocking agents is well known in the Anesthesia literature.…”
Section: Discussionmentioning
confidence: 99%
“…Adverse effects have been documented in patients receiving combined lithium and ECT treatment, and include prolonged seizures [3][4][5][6][7][8][9][10][11] prolonged apnea [5], serotonin syndrome with focal seizures [8], delirium [6,[12][13][14][15] and declining cognition [9,10]. Other studies have shown no adverse effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation